New dynamic load balancing method based on roulette wheel selection and its implementation - ZOU Yuan-ping1; LIU Hong-lin2 (Tongxin xuebao)
A new dynamic load balancing method based on roulette wheel selection in multi-services network was pro-posed.There were two stages in the method,static resource configuration and dynamic route selection.In the first,the optimization distribution of traffic trunk on parallel LSP was obtained by offline optimization algorithm.In the second,the LSP was selected by roulette wheel selection.The simulation results show that the method is able not only to guaran-tee QoS of the services but also balance the network load dynamically.